(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
The properties of clay that influence the soil geotechnical behaviour are fundamentally determined by the physio-chemical characteristics of the composite minerals and the relative proportion in which the minerals are present. It requires a number of sophisticated laboratory equipment and time to determine these characteristics. However, an alternative and all-encompassing method which combines simple and normal laboratory tests that gives a quantitative measure of the composite effect of all the basic properties of clay, termed Clay Colloidal Activity was used in this study. It is an index property, the ratio of plasticity index to clay fractions that combines the Atterberg Limits and the particle size distribution, computed by using the normal routine laboratory tests. In this study, the Clay Colloidal Activity of soil samples collected from Dunde, Belel and Sorau in Maiha Local Government Area of Adamawa State, Northeastern Nigeria were tested. The moisture content of the soils ranged from 10.3% to 12.6%. Plasticity Index for the soils studied ranges from 16 to 25, while the ratio of Moisture Content to Liquid Limit was from 0.21 and 0.35. These values suggested low risk of liquefaction thereby mitigating the possibilities of danger and associated unfavorable engineering issues. Dunde has Colloidal Activity value of 0.80, Sorau has 1.25 and Bele has 1.09. All of them were found to have clay of moderate values of Clay Colloidal Activity, and are considered normal clays that may not pose danger to engineering projects.